Determination, identification of bioactive compounds extracts from yellow banana peels and used in vitro as antimicrobial - Alaa Niamah (International Journal of Phytomedicine, 2014)
In this study, bioactive compounds of six solvent different extracts, from the dry yellow banana peels were present. Methanol was the best solvent extraction .The yield extract , total phenolic content and flavonoids concentration were 1.96 g, 81.89 mg G.A./g and 55.44mg RU/g from extract . The FT-IR spectra were recorded pronounced peaks belonging to the vibration of 3361 cm-1, 1662 cm-1and 1231 cm-1 in the spectra corresponds to the characterized peaks of flavonoids. GC-Ms chromatography clearly show the presence 17 component This analysis revealed that methanolic extract contain Pyrogallol (22.24%), Cis-9-Hexadecenal (21.20%) , Pentadecanoic acid (18.81%), Benzoic acid (16.04%) , Octadecanoic acid (6.18%) and Cis-9-Hexadecenoic acid (4.40%) . 300 mg / ml concentration from methanolic extract had broad inhibitory spectrum against gram positive and negative bacteria , yeast and molds .